2002
DOI: 10.1046/j.1365-3156.2002.00936.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo drug resistance of falciparum malaria in mining areas of Venezuela

Abstract: SummaryThe Lot Quality Assurance Double-Sampling Plan (LQADSP) technique was used in three areas, Maripa, Kiló metro 88 and Ikabaru, to assess the efficacy of antimalarials used routinely by the Venezuelan Malaria Programme. The use of chloroquine (25 mg/kg), chloroquine (40 mg/kg) and the combination of sulfadoxine (500 mg) and pyrimethamine (25 mg) registered treatment failures above the threshold level of 25% in Maripa and Kiló mertro 88. In Ikabaru the use of chloroquine (40 mg/kg) did not surpass that qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 3 publications
1
11
0
Order By: Relevance
“…This efficiency is much higher than that estimated for P. vivax in Western Venezuela, where only 0.32% of infective bites infected a person (RubioPalis et al 1992). On the other hand, the high incidence reported for the study area might also be due to failure to complete treatment and/or multiple drug resistance (Caraballo & Rodríguez-Acosta 1999, Aché et al 2002.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This efficiency is much higher than that estimated for P. vivax in Western Venezuela, where only 0.32% of infective bites infected a person (RubioPalis et al 1992). On the other hand, the high incidence reported for the study area might also be due to failure to complete treatment and/or multiple drug resistance (Caraballo & Rodríguez-Acosta 1999, Aché et al 2002.…”
Section: Discussionmentioning
confidence: 99%
“…The biting rate, sporozoite rate and EIR are so low that these parameters would not be a practical indicator of the efficacy of control campaigns in this area. The control of malaria in the municipality of Sifontes is complex due to its highly mobile population (Aché et al 2002, Moreno et al 2007), the circulation of P. falciparum strains with multidrug resistance (Caraballo & Rodríguez-Acosta 1999, Aché et al 2002), houses with incomplete or no walls in miners' camps and Amerindian villages and the outdoor biting and resting behavior of the principal vectors (Moreno et al 2007). New approaches should be developed that take into consideration legislation on illegal mining, education, community participation and rapid diagnosis and effective treatment where monitoring of drug resistance is essential.…”
Section: Discussionmentioning
confidence: 99%
“…In Uganda, the 28-day genotype-corrected failure rate was 23%; some failures may have been due to poor treatment compliance, but no association between measures of compliance and treatment efficacy was identified (1). On the other hand, some studies have shown excellent efficacy for quinine, including over 95% success after 14 to 28 days for the treatment of falciparum malaria in Equatorial Guinea (45), in Venezuela (2), and in returned travelers in France (32). Second, quinine is poorly tolerated, especially later in the course of 7 days of treatment, suggesting that noncompliance with full treatment courses is common (19,50).…”
mentioning
confidence: 99%
“…A mutation of the CQ resistance gene pfcrt at codon 76 (pfcrt-76) has been associated with reduced susceptibility to QN in vitro, although transfection studies have shown conflicting results (16,37). A seminal study on the association of polymorphisms in pfnhe, a sodium hydrogen exchanger gene, and the in vitro activity of QN indicated that an increase in the number of DNNND repeats (1)(2)(3)(4)(5) in an ms4760 microsatellite was associated with reduced susceptibility to QN (10), and this finding was confirmed recently (13). Variations in the copy number of this repeat in isolates from areas where QN efficacy is known to be reduced in vivo have also been reported (41).…”
mentioning
confidence: 99%